Minimal residual disease analysis by eight-color flow cytometry in relapsed childhood acute lymphoblastic leukemia - Karawajew, L.; Dworzak, M.; Ratei, R.; Rhein, P.; Gaipa, G.; Buldini, B.; Basso, G.; Hrusak, O.; Ludwig, W.-D.; Henze, G.; Seeger, K.; von Stackelberg, A.; et al. (Haematologica (Roma), 2015)
Multiparametric flow cytometry is an alternative approach to the polymerase chain reaction method for evaluating minimal residual disease in treatment protocols for primary acute lymphoblastic leukemia. Given considerable differences between primary and relapsed acute lymphoblastic leukemia treatment regimens, flow cytometric assessment of minimal residual disease in relapsed leukemia requires an independent comprehensive investigation. In the present study we addressed evaluation of minimal residual disease by flow cytometry in the clinical trial for childhood relapsed acute lymphoblastic leukemia using eight-color flow cytometry. The major challenge of the study was to reliably identify low amounts of residual leukemic cells against the complex background of regeneration, characteristic of follow-up samples during relapse treatment. In a prospective study of 263 follow-up bone marrow samples from 122 patients with B-cell precursor acute lymphoblastic leukemia, we tested various B-cell markers, adapted the antibody panel to the treatment protocol, and evaluated its performance by a blinded parallel comparison with the polymerase chain reaction data. The resulting eight-color single-tube panel showed a consistently high overall concordance (P<0.001) and, under optimal conditions, sensitivity similar to that of the reference polymerase chain reaction method. Overall, evaluation of minimal residual disease by flow cytometry can be successfully integrated into the clinical management of relapsed childhood acute lymphoblastic leukemia either as complementary to the polymerase chain reaction or as an independent risk stratification tool. ALL-REZ BFM 2002 clinical trial information: NCT00114348.